The Role of Vitamin D in Preventing Colorectal Carcinogenesis: A Review of Molecular Mechanisms - Herdian, Fauzan; Radityamurti, Fahmi; Permata, Tiara Bunga Mayang; Handoko, Handoko; Kodrat, Henry; Nuryadi, Endang; Wibowo, Heri; Gondhowiardjo , Soehartati (Journal of Pharmacy and Nutrition Sciences, 2021)
Introduction: Colorectal carcinoma is one of the cancers with a high disease burden globally. Previous observational studies have found a connection between colorectal cancer incidence with sunlight exposure and vitamin D levels. Subsequent studies investigated this relationship further and found various anti-tumoral pathways regulated by vitamin D in colorectal tissue. This paper aims to elucidate the actions of those pathways in preventing the malignant transformation of the colorectal cell by reviewing relevant literature. Methods: A search was conducted on several medical literature electronic databases for original research studying the effects of vitamin D treatment on colorectal adenoma and colorectal cancer and its underlying anti-tumoral mechanism. A total of 122 studies were included for evaluation. Results: Twenty-seven studies passed for analysis. These in vitro and in vivo study reveals that vitamin D treatment can suppress cell proliferation, induce apoptosis, maintain cellular differentiation, reduce the pro-inflammatory response, inhibit angiogenesis, and hinder metastatic progression in colorectal cancer and colorectal adenoma cells by regulating associated gene transcription or directly prevents activation of selected signalling pathways. Five studies have also shown that adding calcium to vitamin D treatment increases the anti-tumoral activity of vitamin D through cross-talk between both of their pathways. Conclusion: Vitamin D could potentially impede colorectal cancer transformation and growth through interaction with various signalling pathways and regulating gene transcription. Further clinical studies are needed to confirm whether vitamin D can be used as the basis of targeted colorectal cancer therapy using its inherent anti-tumoral properties.